1994
DOI: 10.1142/s0217732394000538
|View full text |Cite
|
Sign up to set email alerts
|

Note on N = 0 String as N = 1 String

Abstract: A similarity transformation, which brings a particular class of the N = 1 string to the N = 0 one, is explicitly constructed. It enables us to give a simple proof for the argument recently proposed by Berkovits and Vafa. The N = 1 BRST operator is turned into the direct sum of the corresponding N = 0 BRST operator and that for an additional topological sector. As a result, the physical spectrum of these N = 1 vacua is shown to be isomorphic to the tensor product of the N = 0 spectrum and the topological sector… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 4 publications
3
56
0
Order By: Relevance
“…The quantum version of the canonical transformation here described has been also found in a recent paper by Ishikawa and Kato [7].…”
supporting
confidence: 68%
“…The quantum version of the canonical transformation here described has been also found in a recent paper by Ishikawa and Kato [7].…”
supporting
confidence: 68%
“…Anyway, along with the results on explicit evaluation of topological singular vectors in the sl(2) terms, this partial argument in favour of the one-to-one correspondence between the singular states strongly suggests that the sl(2) Kač-Moody algebra and the topological conformal algebra possess identical singular vectors (when c = 3, see the next section). Recall also that 'the same' ordinary matter theory enters our constructions for the topological algebra (section 2) and the sl (2) As noted above, it would be interesting to understand these relations not just between the singular states, but rather between the corresponding algebras, in the context of universal string theory [27,28,29].…”
Section: The Evaluationmentioning
confidence: 98%
“…By adding fermionic gauge fields to the bosonic string, it was recently shown that an N=1 superconformal algebra could be constructed [1], and that the cohomology of the corresponding N=1 BRST charge coincides with the cohomology of the original bosonic string [2,3]. Furthermore, it was shown that the N=1 prescription for calculating scattering amplitudes with this special choice of matter fields produces the usual bosonic string amplitudes [1,3], allowing one to view the bosonic string as a background of N=1 strings.…”
mentioning
confidence: 99%